Problematika Pembuktian Materiil Dan Logika Hukum Tindak Pidana Santet Di Persidangan - Denies Salwani; Muhammad Dede Al Farabi Suardi; Ariel Lian Pratama Reksa; Muhammad Fajar Lutfi Raihan; Amos Saito Hamonangan Simorangkir (CV. ITTC INDONESIA, 2026)
This study aims to analyze the shift in legal paradigms and evidentiary issues related to the criminalization of black magic in Law Number 1 of 2023 concerning the Criminal Code (New Criminal Code). The phenomenon of supernatural powers has long been a social reality in Indonesia, but often causes conflict due to limited regulations in the old Criminal Code. This study uses a qualitative descriptive-analytical method to examine the legal transformation in Article 252 of the New Criminal Code, which classifies the practice of supernatural powers as a crime against public order. The results show that the article uses a formal criminal offense construction, namely emphasizing the act of admitting, offering, or promising the services of supernatural powers that can cause physical or mental suffering. This approach is a pragmatic solution to overcome the difficulty of proving a causal relationship between the practice of black magic and its impacts scientifically. This study concludes that this criminalization provides legal certainty for the practice of shaman fraud, but still has the potential to cause injustice due to subjective interpretations of judges and differences between modern legal reasoning and public beliefs. Therefore, innovation in the justice system is needed through the integration of cross-disciplinary expert testimony to strengthen evidence without ignoring the socio-cultural values of society.